The impact of comorbidities on selexipag treatment effect in patients with pulmonary arterial hypertension: insights from the GRIPHON study. (21st November 2021) - Rosenkranz, Stephan; Channick, Richard; Chin, Kelly M.; Jenner, Bartosz; Gaine, Sean; Galiè, Nazzareno; Ghofrani, Hossein‐Ardeschir; Hoeper, Marius M.; McLaughlin, Vallerie V.; Du Roure, Camille; Rubin, Lewis J.; Sitbon, Olivier; et al.
Abstract: Aims: The number of pulmonary arterial hypertension (PAH) patients with comorbidities is increasing and there are limited data on response to PAH‐targeted therapies in this population. These post hoc analyses explored the effect of selexipag in PAH patients with cardiovascular comorbidities in the GRIPHON study. Methods and results: Randomized patients ( n  = 1156) were classified using three methods: (i) by subgroups defined according to previously published comorbidity count and restrictive haemodynamic criteria: Subgroup A (<3 comorbidities and haemodynamic criteria met; n  = 962) and Subgroup B (≥3 comorbidities and/or haemodynamic criteria not met; n  = 144); comorbidities included body mass index ≥30 kg/m 2, essential hypertension, diabetes, history of coronary artery disease; (ii) by number of comorbidities, with addition of atrial fibrillation (0, 1, 2, 3, 4, or 5); (iii) by presence of individual comorbidities. Selexipag to placebo hazard ratios (HR) and 95% confidence intervals (CI) for morbidity/mortality (primary composite endpoint) were estimated using Cox regression adjusting selexipag effect for baseline covariates. Approximately half of the patients in GRIPHON ( n  = 584; 50.5%) had comorbidities. Selexipag reduced the risk of a morbidity/mortality event compared with placebo in both Subgroup A (HR 0.66, 95% CI 0.53, 0.82) and Subgroup B (HR 0.50, 95% CI 0.26, 0.96), with no evidence of an inconsistent treatment effect between subgroups (interaction p  = 0.432). Consistent results were observed in analyses by number and by specific type of comorbidity. Conclusion: Selexipag reduces the risk of a morbidity/mortality event vs. placebo irrespective of patient comorbidity status, suggesting that comorbidity status does not influence the treatment effect of selexipag. Abstract : Selexipag reduced the risk of morbidity/mortality events in patients with pulmonary arterial hypertension (PAH) independently of the patients' comorbidity status. CI, confidence interval; LVEDP, left ventricular end‐diastolic pressure; PAWP, pulmonary arterial wedge pressure; RCT, randomized controlled trial.